Effect of thyroid function on COPD exacerbation frequency: a preliminary study - Ulasli, Sevinc Sarinc; Bozbas, Serife Savas; Ozen, Zeynep Erayman; Ozyurek, Berna Akinci; Ulubay, Gaye (Multidisciplinary Respiratory Medicine, 2013)
Background: Frequent exacerbations of chronic obstructive pulmonary disease (COPD) have negative effects on quality of life and survival. Thus, factors related to exacerbations should be determined. We aimed to evaluate the effects of thyroid function on quality of life and exacerbation frequency in COPD patients. Methods: The study population (n = 128) was divided into 3 groups (Group 1: COPD patients with hypothyroidism (n = 44); Group 2: COPD patients with normal thyroid function tests (n = 44); Group 3: Healthy subjects (n = 40)). Pulmonary function tests, maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP) measurements were performed. Quality of life questionnaire (Short Form 36, SF-36) was carried out. Patients were followed up for one year and number of exacerbations was recorded. Results: FVC, FEV1/FVC, and FEF 25–75% measurements were statistically different between group 1 and 2 (p = 0.041, p = 0.001, p = 0.009 respectively). Although MEP values were significantly different between group 1 and 2 (p = 0.006), there was no significant difference in MIP values between groups (p = 0.77). Quality of life scores in group 1 and 2 were significantly lower than control group. Exacerbation frequency was significantly higher in group 1 than in group 2 (p = 0.017). TSH values and exacerbation frequency had positive correlation (p < 0.0001; r = 0.82). Conclusions: The results of the present study suggest that thyroid function has an effect in exacerbation frequency of COPD. Decrease in exacerbation numbers with early detection of impairment in thyroid function will have positive contribution on quality of life in COPD patients.